ANALYSIS OF FACTORS AFFECTING EMPLOYEE PERFORMANCE: A STUDY AT THE MINISTRY OF RELIGION OF BOJONEGORO REGENCY - Rosihan, Ahfan Ihza; Octavia, Ayu Nurafni (Universitas Wahid Hasyim Semarang, 2025)
The purpose of this study is to determine how the influence of performance appraisal, leadership style, and work motivation on employee performance at the Ministry of Religious Affairs of Bojonegoro Regency. This study is expected to be able to help identify the main factors of the problem of declining performance. The sampling technique used in this study is Purposive Sampling, which is a technique for determining samples with certain considerations. The analysis used in this study is Multiple Linear Regression Analysis, where previously the validity test, reliability test and classical assumption test were carried out. In this study used 33 respondents. This study used SPSS to conduct statistical tests to obtain conclusions in determining which independent variables will affect the dependent variable. The results of this study indicate that performance appraisal does not affect employee performance, leadership style has a positive and significant effect on employee performance and work motivation has a positive and significant effect on employee performance